Juridical Review of the Role of Society Against Sexual Crimes of Minors Through Gadgets Based on Law Number 19 of 2016 concerning Information and Electronic Transactions - Sahedi Sahedi; Sandi Aprianto; Widya Timur (Fakultas Hukum Dehasen, 2023)
Human rights in Indonesia are highly respected, where children's rights are included and marked by the guarantee of protection and fulfillment of children's rights in the 1945 Constitution of the Republic of Indonesia and several laws and regulations. One of the important rights that children should have is the right to get legal protection, where rights are given to children who experience abuse, exploitation, crime/violence, child trafficking, neglect, children living in conflict-prone areas, vulnerable to disasters and other laws. In 2019, the Ministry of Women's Empowerment and Child Protection (Kemen PPPA) recorded 6,454 children being victims of sexual violence. This number increased in 2020 by 8.14 percent. Then in 2021, the increase will be 25.07 percent. The Ministry of Women's Empowerment and Child Protection (Kemen PPPA) received 10,727 reports of cases of violence against women and children. As many as 11,604 people become victims of sexual violence in 2022, namely 56.5 percent of children become victims. What is the role of the community towards sexual crimes of minors through gadgets based on law number 19 of 2016 concerning information and electronic transactions in reducing sexual crimes. Sexual crime is a crime that is quite high in Indonesia which causes trauma, depression and death. The legal research methodology used is normative legal research or library research. Based on this theory of legal protection, the authors analyze that the use of gadgets by children is mostly uncontrolled. So that it is easier for children to access websites related to sexuality. Because minors are people who are not competent in law, the use of gadgets must be supervised by parents so that they are not used as an example by minors. This is where the role of the government is to be able to block games related to sex, then there are videos like on social media that should be blocked. In addition, the community must be educated about the dangers of using gadgets for the future of children, but on the other hand, there are also positive impacts. The author analyzes that the role of the community is very influential in reducing the number of sexual crimes against minors, because the community has direct contractors, especially parents, relatives and the closest environment who have minors but are required to use gadgets for school purposes, given the changing times and increasingly sophisticated technology.